A study on convergence of international employee rights within human resources management practices in Bangladesh - Andalib, Tarnima Warda (2018)
This research observes the Human Resources Management (HRM) policies and practices of the Bangladeshi manufacturing companies along with the parallel existing International employee rights‘ standards like UDHR (Universal Declaration of Human Rights), ILO (International Labour Organization), Bangladesh Labour Law (BDL) and etc and develops a converged HRM framework to facilitate the HR managers a comprehensive understanding regarding HRM and their decision making process. HRM policies and practices of company seem to be quite distinct, which are consisting of HRM factors, HRM models (developed by various scholars) and HRM perspectives (required by the organizations). Meanwhile, International employee rights‘ platforms are consist of employee rights law and regulations those are either addressed or not addressed by the HR managers while implementing the HRM policies into practices. Ofcourse, different organizations treat their employees differently and different HR managers have different understanding about the HRM approaches. This research firstly intends to find the perspectives of the HRM policies and HRM practices (consist of HRM factors, HRM models) of the manufacturing companies of Bangladesh, secondly intends to map these perspectives with Employee Rights (ERS) protocols, thirdly wishes to develop HRM framework from mapping and address the followed HRM approaches. This research has undertaken the qualitative method and applied multiple case studies in twelve popular and large scale Bangladeshi manufacturing companies. Eighty seven participants, representing the human resources functional areas and board or chief hierarchical important persons were interviewed to gain explanations about what perspectives were being used by the HRM policies and HRM practices of the organizations and how these were implemented in the manufacturing companies of Bangladesh. This research achieved two findings, which are two distinct HRM approaches and a new HRM framework that provided a comprehensive understanding of HRM to the HR managers in the listed Bangladeshi manufacturing companies‘ context. Therefore, in this research, The HRM framework has converged the found HRM perspectives from the MCS and the related protocols of UDHR, ILO & BDL.